Aproveitamento de subproduto cervejeiro na biossorção do corante Amarelo Reafix B8G: estudos cinético, de equilíbrio e termodinâmico - Delgobo, Emanuele Sansana (2019)
The purpose of this study was to evaluate the efficiency of malt bagasse in the removal of the Reafix B8G (AR-B8G) Yellow textile dye in aqueous solution, using the biosorption technique, performed in a batch system. The tests were subdivided into five stages: characterization tests, operational tests, kinetic, equilibrium and thermodynamic tests. In the first stage, the characterization of biomass morphology was performed before and after biosorption by SEM analysis. From the obtained pHPCZ 6.0 it was found that the removal is favored at acidic pHs. In the second stage it was verified that the pH 2 was more effective to remove the dye AR-B8G. The grain size of the malt bagasse did not significantly affect the percentage of removal, therefore it was decided to use the biomass without screening. In the following steps, the influence of temperature on biosorption was evaluated from tests performed under different times. By kinetics evaluation the equilibrium time of 24 hours was obtained, reaching the removal of about 96% of contaminant. It can be emphasized that from the first 10 minutes, biosorption was greater than 50% and in 60 minutes the removal of AR-B8G dye was greater than 90%. The Pseudo-Second Order kinetic model fitted the experimental data better. The process was characterized as exothermic and spontaneous from the enthalpy and free energy parameters of Gibbs, respectively, indicating that the biosorption was favorable from the thermodynamic point of view. The activation energy of 28.0182 kJ mol-1 showed that the removal occurred by physisorption. The equilibrium isotherm that best characterized the experimental data was the Langmuir-BET isotherm. Actual effluent testing achieved removal by about 74% despite high COD. With the obtained results, it was proposed an alternative to reduce the environmental impacts from the textile industries, by optimizing the effluent treatment processes, making room for the development of new sustainable technologies, within the context of the circular economy.